Helmet use and risk of head injuries in alpine skiers and snowboarders: changes after an interval of one decade - Sulheim, S.; Ekeland, A.; Holme, I.; Bahr, R. (British Journal of Sports Medicine, 2017)
Background: In a previous study, we concluded that a safety helmet can reduce the risk for head injury by 60%. Other studies reported similar effects, resulting in a general recommendation to wear a helmet while skiing or snowboarding.